2012
DOI: 10.3724/sp.j.1005.2012.00551
|View full text |Cite
|
Sign up to set email alerts
|

Biological function of the Somatic embryogenesis receptor-like kinases in plant

Abstract: Somatic Embryogenesis Receptor-Like Kinases (SERKs) belong to the LRR-RLK II subfamily, which contain three conserved domains: an extracellular domain, a transmembrane domain, and an intracellular catalytic kinase domain. Previous studies had found that SERKs play many roles during plant development. This review made a brief introduction about the character of the SERKs and described the biological function of these proteins in somatic embryogenesis, sporogenesis, hormone response and host defense response. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…They are also involved in plant development, somatic embryogenesis, sporogenesis, hormone response, and host defense response (Shi et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…They are also involved in plant development, somatic embryogenesis, sporogenesis, hormone response, and host defense response (Shi et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that SERKs play multiple roles in growth, development, and apomixis in plants Shi et al, 2012). In our research, we discovered that MhSERK1 and MhdSERK1 were highly expressed in the ovary of Pingyi Tiancha and the hybrid strain (33#), respectively.…”
Section: Discussionmentioning
confidence: 67%
“…Albertini et al (2005) demonstrated that expression of PpSERK was different in apomictic and sexual genotypes in Poa pratensis1, and thus, PpSERK may be related to apomixis. In addition, Shi et al have shown that once SERK is activated by the nucellar cell near the megasporocyte of amixis, the migrule may induce signal conduction from nucellar cells to the embryo sac development, and the functional somatic embryo produced by meiosis of somatic cells in the ovary could lead to apomixis (Shi et al, 2012). Accordingly, we speculated that, in our study, MhSERK1 and MhdSERK1 might be related to reproduction in Pingyi Tiancha and the hybrid strain (33#), whereas MhSERK1 might play a key role in apomixis in Pingyi Tiancha.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations